(untitled) (Proceedings of the International Conference on Education, 2023)
This research aims to develop teaching materials for foreign students who study Indonesian to improve the language skills of Indonesian Language students for Foreign Speakers (BIPA) at Jenderal Soedirman University based on a project based learning model for beginners (A1) with Folklore culture from Indonesia. So that BIPA students can learn the messages contained in folklore that reflect the local community so that BIPA students can easily adapt in Indonesia. This study uses a research design using the Research and Development (R&D) development model which refers to the ADDIE development model consisting of five main steps, namely Analysis, Design, Development, Implementation, and Evaluation. Based on the research results, it can be concluded that (1) the results of the validation of material experts obtained a value of 94% and were included in the valid criteria and were suitable for use for learning, (2) the results of the validation of Information and Technology (IT) experts obtained a value of 92% and were included in the valid and feasible criteria used for learning, (3) the validation results of linguists obtained a validity value of 96% and included in the valid criteria and were suitable for use for learning, and (4) practitioners’ responses obtained a value of 94.00% and BIPA students obtained a value of 95.00% so that it was declared appropriate and accepted as teaching material.